Greenland, view of Kjerulf Fjord through to Dicksons Fjord annotated by Louise A. Boyd - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background; north side of L.A.B.'s Scoop Mt. [Mountain] showing both scoops and part of double wishbone snow-patch, as seen in 26-H-11 & 22-D-5. Photo taken on S.E. side of southern terminal of mts. [mountains] which have formed eastern side of Kjerulfs [Kjerulf] Fjord; looking S.E.